2022
DOI: 10.3390/ani12080975
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heat Stress on Bovine Sperm Quality and Competence

Abstract: Global warming has negatively influenced animal production performance, in addition to animal well-being and welfare, consequently impairing the economic sustainability of the livestock industry. Heat stress impact on male fertility is complex and multifactorial, with the fertilizing ability of spermatozoa affected by several pathways. Among the most significative changes are the increase in and accumulation of reactive oxygen species (ROS) causing lipid peroxidation and motility impairment. The exposure of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…Formation of the two sperm cells is the central developmental process occurring at the bicellular stage. Disruption of spermatogenesis in mammals due to HS has been shown to negatively impact male reproduction altering sperm morphology and leading to DNA fragmentation (Hansen, 2009; Garcia-Oliveros et al, 2020; Capela et al, 2022). In plants little is known on the impact of high temperatures for sperm cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of the two sperm cells is the central developmental process occurring at the bicellular stage. Disruption of spermatogenesis in mammals due to HS has been shown to negatively impact male reproduction altering sperm morphology and leading to DNA fragmentation (Hansen, 2009; Garcia-Oliveros et al, 2020; Capela et al, 2022). In plants little is known on the impact of high temperatures for sperm cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms responsible for the occurrence of testicular heat stress is the increase in ambient temperature provided by global climate change (140). Given this condition, several studies have reported the negative effects of increased environmental temperatures on male reproduction (141).…”
Section: Consequences Of Increased Testicular Temperature Due To Clim...mentioning
confidence: 99%
“…Such bulls showed clear evidence that a warm environment can lead to a decrease in sperm morphology and motility [49]. In addition, it is clear that reactive oxygen species generation are involved [50].…”
Section: Is "Heat-stress" Physiologically Relevant?mentioning
confidence: 99%